Oligosoma aureocola sp. nov. (Reptilia: Scincidae) from the northern Southland high country of Aotearoa/New Zealand - Knox, Carey; Patterson, Geoff B.; Chapple, David G. (Zootaxa, 2023)
A species of diurnal skink from the Mataura Range and Mid Dome in central northern Southland, Aotearoa/New Zealand is described as Oligosoma aureocola sp. nov. It is a small species, coloured mid- to dark brown with smooth longitudinal stripes, and lives along rocky alpine ridges, low-stature shrublands, and tussock grasslands. This skink is a conspicuous species, easily sighted basking and foraging in talus or alpine plants such as golden spear grass (Aciphylla aurea).